Physician support for diabetes patients and clinical outcomes - Ciechanowski Paul; Lin Elizabeth HB; Ludman Evette J; Seelig Michelle D; Rutter Carolyn M; Von Korff Michael; Gensichen Jochen; Young Bessie A; Wagner Edward H; Katon Wayne J (BMC, 2009)
Abstract Background Physician practical support (e.g. setting goals, pro-active follow-up) and communicative support (e.g., empathic listening, eliciting preferences) have been hypothesized to influence diabetes outcomes. Methods In a prospective observational study, patients rated physician communicative and practical support using a modified Health Care Climate Questionnaire. We assessed whether physicians' characteristic level of practical and communicative support (mean across patients) and each patients' deviation from their physician's mean level of support was associated with glycemic control outcomes. Glycosylated haemoglobin (HbA1c) levels were measured at baseline and at follow-up, about 2 years after baseline. Results We analysed 3897 patients with diabetes treated in nine primary care clinics by 106 physicians in an integrated health plan in Western Washington, USA. Physicians' average level of practical support (based on patient ratings of their provider) was associated with significantly lower HbA1c at follow-up, controlling for baseline HbA1c (p = .0401). The percentage of patients with "optimal" and "poor" glycemic control differed significantly across different levels of practical support at follow (p = .022 and p = .028). Communicative support was not associated with differences in HbA1c at follow-up. Conclusion This observational study suggests that, in community practice settings, physician differences in practical support may influence glycemic control outcomes among patients with diabetes.